Quantum dynamics of excitations and decoherence in many-spin systems detected with Loschmidt echoes: its relation to their spreading through the Hilbert space - Sánchez, Claudia Marina (2016)
Fil: Sánchez, Claudia Marina. Universidad Nacional de Córdoba. Facultad de Matemática, Astronomía, Física y Computación; Argentina.